2010
DOI: 10.1016/j.vetpar.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eimeria acervulina infection history on the immune response and transmission in broilers

Abstract: Heterogeneity in exposure to Eimeria spp. of chickens in a flock will result in differences between individual birds in oocyst output and acquired immunity, which subsequently affects transmission of the parasite in the population. The aim of this study was to quantify effects of previous infection of broilers with Eimeria acervulina on immune responses, oocyst output and transmission. A transmission experiment was carried out with pair-wise housed broilers, that differed in infection history. This "infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…From this strategy (even compromising the identification of lesions in broiler intestines in accordance with the pre-patent period of the parasites as proposed by Johnson and Reid (1970)), it allowed our group to assess the effects of treatments on intestinal lesions and, at the same time, allow seeders to infect fellow broilers by contact (Velkers et al . 2010) imitating the natural transmission pathway on commercial farms, which was the objective of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this strategy (even compromising the identification of lesions in broiler intestines in accordance with the pre-patent period of the parasites as proposed by Johnson and Reid (1970)), it allowed our group to assess the effects of treatments on intestinal lesions and, at the same time, allow seeders to infect fellow broilers by contact (Velkers et al . 2010) imitating the natural transmission pathway on commercial farms, which was the objective of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Broiler seeders were artificially challenged with dual coccidial infections at 8 days of age and euthanized for lesion scoring 9 days post inoculation, allowing sufficient time to contaminate the litter in each pen in accordance with the prepatent period of E. acervulina and E. maxima parasites (Eckert et al 1995). From this strategy (even compromising the identification of lesions in broiler intestines in accordance with the pre-patent period of the parasites as proposed by Johnson and Reid (1970)), it allowed our group to assess the effects of treatments on intestinal lesions and, at the same time, allow seeders to infect fellow broilers by contact (Velkers et al 2010) imitating the natural transmission pathway on commercial farms, which was the objective of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary infection can reduce significantly the occysts excretion in a subsequent secondary infection. The birds infected naturally by contact have shown that even a low occysts excretion may cause infections by contact, and the level of occysts expelled will depend on the condition of acquired immunity (Velkers et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Entre estes mecanimos tem-se a barreira epitelial mucosa, fagócitos e outros leucócitos, citocinas e componentes do sistema complemento (YUN et al, 2000). Todavia, o principal meio de controle da doença é através do uso de drogas anticoccidianas, associada com vacinas vivas atenuadas (VELKERS et al, 2010 GIANNENAS et al, 2003;NAIDOO et al, 2008;LEE et al, 2011;ALMEIDA et al, 2012;KIM et al, 2013 O produto utilizado contendo o β-ácido possui concentração de 30%, ou seja, para obter a dosagem de β-ácido especificado utilizou-se 100, 200, 400 e 800 mg/kg do produto para os tratamentos 3, 4, 5 e 6, respectivamente. As concentrações totais de β-ácido detectado nas dietas experimentais estão apresentadas na Tabela 2.…”
Section: Palavrasunclassified